The Ratio of Red Blood Cell Distribution Width to Albumin Is Correlated With All-Cause Mortality of Patients After Percutaneous Coronary Intervention – A Retrospective Cohort Study - Weng, Yingbei; Peng, Yangpei; Xu, Yuxuan; Wang, Lei; Wu, Bosen; Xiang, Huaqiang; Ji, Kangting; Guan, Xueqiang (Frontiers in Cardiovascular Medicine, 2022)
Objectives The purpose of this study was to investigate the independent effect of the ratio of red blood cell distribution width (RDW) to albumin (RA) on all-cause mortality in patients after percutaneous coronary intervention (PCI). Methods Clinical data were obtained from the Multiparameter Intelligent Monitoring in Intensive Care-III (MIMIC-III) database version 1.4 and the database of Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University. We used the MIMIC-III database for model training, and data collected from the Second Affiliated Hospital of Wenzhou Medical University for validation. The primary outcome of our study was 90-day mortality. Cox proportional hazards regression model was used to estimate hazard ratio (HR) for the association between RA and all-cause mortality in patients after PCI. Pearson correlation analysis was conducted to assess the relationship between RA and Gensini score or cardiac troponin I (cTnI). Results A total of 707 patients were eligible in MIMIC-III database, including 432 males, with a mean age of 70.29 years. For 90-day all-cause mortality, in the adjusted multivariable model, the adjusted HRs [95% confidence intervals (CIs)] for the second (RA: 3.7–4.5 ml/g) and third (RA >4.5 ml/g) tertiles were 2.27 (1.11, 4.64) and 3.67 (1.82, 7.40), respectively, compared to the reference group (RA <3.7 ml/g) (p < 0.05). A similar relationship was also observed for 30-day all-cause mortality and 1-year all-cause mortality. No significant interaction was observed in subgroup analysis. Receiver operating characteristic (ROC) curve analysis proved that the ability of RA to predict the 90-day mortality was better than that of RDW or albumin alone. The correlation coefficient between Gensini score and RA was 0.254, and that between cTnI and RA was 0.323. Conclusion RA is an independent risk factor for all-cause mortality in patients after PCI. The higher the RA, the higher the mortality. RA has a good predictive ability for all-cause mortality in patients after PCI, which is better than RDW or albumin alone. RA may be positively correlated with the severity of coronary artery disease (CAD) in patients with CAD.